2016
DOI: 10.1002/2016wr018944
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of optimal sampling design using a modularity strategy

Abstract: In real water distribution networks (WDNs) are present thousands nodes and optimal placement of pressure and flow observations is a relevant issue for different management tasks. The planning of pressure observations in terms of spatial distribution and number is named sampling design and it was faced considering model calibration. Nowadays, the design of system monitoring is a relevant issue for water utilities e.g., in order to manage background leakages, to detect anomalies and bursts, to guarantee service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…To determine the location of flow meters and gate valves, DMA design was optimized based on each conceptual cut and returned an optimal solution for each one, accounting for hydraulic behavior change in the network with respect to maximizing the reduction of background leakage in each DMA. Using the WDN-oriented modularity index, Simone et al [68] developed a sampling-oriented modularity index to perform optimal spatial distribution and assess the optimal number of pressure meters needed in a network (i.e., sampling design) using a multi-objective optimization method to minimize pressure-meter cost versus sampling-oriented modularity.…”
Section: Modularity-based Algorithmmentioning
confidence: 99%
“…To determine the location of flow meters and gate valves, DMA design was optimized based on each conceptual cut and returned an optimal solution for each one, accounting for hydraulic behavior change in the network with respect to maximizing the reduction of background leakage in each DMA. Using the WDN-oriented modularity index, Simone et al [68] developed a sampling-oriented modularity index to perform optimal spatial distribution and assess the optimal number of pressure meters needed in a network (i.e., sampling design) using a multi-objective optimization method to minimize pressure-meter cost versus sampling-oriented modularity.…”
Section: Modularity-based Algorithmmentioning
confidence: 99%
“…The edge closeness is a measure of the edge efficiency in spreading the information, and it consists in considering the distance between pipes rather than between nodes. To this aim, one can refer to the line graph or the edge adjacency matrix, which represents the adjacencies between edges of the network (Simone et al, ). Therefore, the formulation is ClC=1edl,e where C l C is the edge closeness of the edge l and ∑ d l,e is the sum of the steps (path) from edge l to edges e of the network.…”
Section: Tailoring Centrality Metrics For Wdns: Node Versus Edge Cenmentioning
confidence: 99%
“…Although a few studies have identified a tradeoff relationship between the meter cost and detection effectiveness measure-mostly by using a constrained single-objective model [9,10,17]-DP-type measures (e.g., MeterRob or DP) and RF have not previously been optimized simultaneously. The non-dominated sorting genetic algorithm-II (NSGA-II) [18] was used to explore the tradeoff relationship between the objectives of the MOMP model.…”
Section: Multi-objective Optimal Meter Placement (Momp) Modelmentioning
confidence: 99%